1. The problem statement, all variables and given/known data Show how W= (P2V2 - P1V1) / [itex]\gamma[/itex] -1 can be derived using relations between PVgamma = constant, and W(1 to 2) = -[itex]\int[/itex] P(T,V) dV (from v1 to v2). 2. Relevant equations I think we can use R = Cv ([itex]\gamma[/itex] - 1) 3. The attempt at a solution Not sure how to start. The integral would be W = [itex]\int[/itex] P2V2 - P1V1 dV, but that means we'd have to do partial differential equations, and the problem is not meant to be so difficult. Any suggestions?